Polymorphisms of ACMSD-TMEM163, MCCC1, and BCKDK-STX1B Are Not Associated with Parkinson’s Disease in Taiwan - Fung, Hon-Chung; Chen, Yi-Chun; Chen, Chiung-Mei; Chang, Kuo-Hsuan; Wu, Yih-Ru (Parkinson's disease, 2019)
Previous genome-wide association studies in Caucasian populations suggest that genetic loci in amino acid catabolism may be associated with Parkinson’s disease (PD). However, these genetic disease associations were limitedly reported in Asian populations. Herein, we investigated the effect of top three PD-associated genetic variants related to amino acid catabolism in Caucasians listed on the top risk loci identified by meta-analysis of genome-wide association studies in PDGene database, including aminocarboxymuconate-semialdehyde decarboxylase- (ACMSD-) transmembrane protein 163 (TMEM163) rs6430538, methylcrotonyl-CoA carboxylase 1 (MCCC1) rs12637471, and branched-chain ketoacid dehydrogenase kinase- (BCKDK-) syntaxin 1B (STX1B) rs14235, by genotyping 599 Taiwanese patients with PD and 598 age-matched control subjects. PD patients demonstrate similar allelic and genotypic frequencies in all tested genetic variants. These ethnic discrepancies of genetic variants suggest a distinct genetic background of amino acid catabolism between Taiwanese and Caucasian PD patients.